DEVELOPMENT OF MULTIPLE REPRESENTATION BASED E-MODULS TO IMPROVE ABSTRACT THINKING SKILLS PHYSICS OF HIGH SCHOOL STUDENTS - Rosynanda Nur Fauziah; Abu Yazid Raisal (Universitas Negeri Medan, 2022)
Students' multi-representational understanding in understanding glasses needs to be raised by educators in various forms of presenting information so that students are able to understand an abstract problem to become concrete in all realms of reflection. One way to apply learning with a multi-representational approach can have a positive influence on students' cognitive abilities which include low cognitive levels and high cognitive levels. The purpose of this research is to develop an e-module of based on multiple representations for high school students' abstract thinking skills. This is to determine the success of module development that has been designed in such a way. The research method used is research and development or research and development. The model used in the development of this e-module is a 4D model which consists of four stages of development, name define, design, develop, and disseminate. The stages used in the development of this e-module reach the develop stage, due to research limitations and in accordance with the research objectives, namely the development of e-modules. From the results of the research and discussion, it can be concluded that several representation-based e-modules to improve the abstract thinking skills of high school students that have been compiled are of good quality and still need to be achieved. . The average test results of material validation experts stated that the module was in the good category with an average value of 3.5 on a Likert scale, then for the media validation results it was also with an average of 3.5 and said to be in a good category